Tobacco smoking and risk for dementia: evidence from the 10/66 population-based longitudinal study. (1st November 2020) - Otuyama, Leonardo J.; Oliveira, Déborah; Locatelli, Danilo; Machado, Danusa de A.; Noto, Ana Regina; Galduróz, José Carlos Fernandes; Prince, Martin J.; Ferri, Cleusa P.
Abstract: Objective: This study aimed to estimate the association between tobacco smoking and risk for dementia in seven low- and middle-income countries. Methods: Secondary analysis of the 10/66 population-based cohort study was conducted with 11, 143 dementia-free individuals aged 65 years and older who were followed-up for an average of 3.8 years totalling 42, 715 person-years. Cox regression with competing-risk analyses was used, controlling for age, gender, number of assets, past hazardous drinking, exercise and self-report of heart disease. Exposure was measured in packyears and smoking status. The number of packyears was calculated by multiplying the average number of packs per day by years of consumption up to 50 years old and up to age at baseline. Results: Meta-analysis of the results from each country yielded non-significant pooled relative risk ratios for all comparisons. There was no difference in risk for any dementia between 'ever smokers' compared to 'never smokers' (HR 0.96; 95% CI 0.82–1.13); 'current smokers' compared to 'never smokers' (HR 0.83; 95% CI 0.66–1.06); 'former smokers' compared to 'never smokers' (HR 1.06; 95% CI 0.88–1.27); 'current smokers' compared to 'former smokers' (HR 0.86; 95% CI 0.66–1.13). Results were similar for Alzheimer's disease (AD) and Vascular Dementia (VaD) as outcomes. Lifetime tobacco consumption (packyears) was not associated with any dementia (HR 1.00; 95% CI 0.99–1.00), nor with AD or VaD. Conclusion: Pooled results from all the countries showed no significant association between smoking and the onset of any dementia. Selective quitting in later-life might have biased the results towards no effect.